VAPORIZATION ON THE RELIASE OF GROWTH STRESSES IN LOGS OF Eucalyptus dunnii FROM TWO ORIGIN - SEVERO, Elias Taylor Durgante; TOMASELLI, Ivan (Scientia Agraria, 2000)
The objective of this research was to analyze the effect of ringment and vaporization treatments on the release of growth stresses in logs of two Eucalyptus dunnii. In order to do it, a ringment treatment was performed with a chain saw and later, logs were steamed at 100° C for 20 h. The assessment of these treatments effects was done by analyzing measuring the cracks, gaps on boards in relation on the log during the sawing process and warping. The results showed that the treatment was efficient and decreased the gap on the boards in relation to the log, length and size of the splits for both proceedings tested.